Physiological responses of forest species to water stress - Otto, Marina Shinkai Gentil (2015)
Abiotic and biotic stresses affect tree growth and play a major role in determining the geographic distribution of species. The objective of this study is to elucidate the following questions: (1) are GABA aminoacid and stomatal control good indicators of tolerance to water stress in Eucalyptus clones? In addition, what are the anatomical differences between drought-tolerant and drought-sensitive clones of Eucalyptus? (2) Are there differences of xylem vulnerability to cavitation in Pinus flexilis families susceptible and resistant to white pine blister rust (WPBR) and with different origins (high and low altitudes)? Two studies were carried out to elucidate the issues above. On chapters 1, eight Eucalyptus clones from different geographical and climatological conditions, three drought-sensitive (CNB, FIB and JAR), three drought-tolerant (GG, SUZ and VM), and two plastics (VER and COP), were studied in normal water supply (control treatment) and in water stress conditions (stress treatment). The first chapter concluded that GABA is an aminoacid very sensitive to water stress, but there was no relation between GABA concentration and tolerance to water stress of the clones. In addition, all clones decreased stomatal conductance with increasing vapor pressure deficit, and plastics and drought-tolerant clones (except GG) presented lower stomatal sensitivity to vapor pressure deficit under stress conditions than drought-sensitive clones. Besides, all clones showed differences on the anatomical parameters between, and only COP (plastic) and SUZ (drought-tolerant) showed homogeneous mesophyll and amphi-hipostomatic leaves. All clones increased the number of stomata and reduced leaf thickness of the leaves formed after water stress period. On the chapter 2, we studied 12 families of Pinus flexilis originating from high and lower altitudes, in which six families previously shown to contain the dominant C4 allele (resistant to WPBR) and six families without C4 allele (susceptible to WPBR). This study showed that the mean cavitation pressure (MCP) of Pinus flexilis varying between 3.63 a -4.84 Mpa, although there was a significant difference in vulnerability to cavitation comparing all families, this variable was not related to WPBR and origin region. These studies highlight that the physiological responses of plants under water stress conditions are important tools that can be used to complement the strategies of genotype selection in forest breeding programs.